Use of hyperoxidized oils-based medical devices for the wound healing in post-surgical patients - Guarro, Giuseppe; Carella, Sara; Cordellini, Marino (Acta Biomedica Atenei Parmensis, 2023)
Postoperative injuries of the lower limb represent a challenging complication after surgery. The use of advanced dressings, local flaps, reconstructions with grafts or dermal substitutes represent the most common therapeutic solutions. With the present paper, we describe a case of a postoperative wound of the leg treated with the use of hyperoxidized oils-based medical device: NOVOX©. An 88-year-old woman presented in September 2022 an ulcer on her left leg, on the external malleolus. Authors decided to treat the lesion with NOVOX© in the form of a dressing pad. The controls initially lasted every 48 hours, subsequently every 72 hours and in the last month only once a week. The progressive clinical examination showed a global reduction of the wound area. According to our experience, the novel oxygen-enriched oil-based dressing pad (NOVOX©) is simple to use, secure, and successful in treating old patients receiving postoperative therapy for leg ulcers.